Assessment of seed quality and identifying sources of contaminants for maize seed across seed generations accessed through different seed source in Northwest Amhara. - Anbes, Tilaye; Abebe, Dereje; Elmihun, Melkamu; Asredie, Semagn; Ewenetu, Wasihune; Chanie, Yematew (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Genetic purity is one of the quality criteria required for successful seed production of maize. In hybrid seed production, genetic purity can be contaminated by outcrossing from other varieties or events of inbreeding. The objectives of the study are to clearly put sources of contaminants at each seed class level and suggest possible recommendations to maintain seed quality and to test the physical and physiological quality parameters of each seed classes. A multistage sampling technique was applied for this survey study. Total sample size of 160 households from all districts was interviewed and both qualitative and quantitative data was generated on constraints of hybrid maize production in western Amhara region. Filed inspection of maize seed production fields was done. Moreover, seed samples were collected from, company one, company two, company three and company four. Seed quality testing was carried out at Adet agricultural research center seed laboratory in 2021 for the collected samples. Mean percentages of quality parameters were computed and used for comparing the formal seed sources. The survey study indicated that maize seed production in the districts is constrained by a variety of related factors; the most important constraints are insufficient supply, delayed delivery, unavailability of preferred variety. The field inspection showed the presence of contaminants of maize seed at parental lines (inbred lines) and hybrid seed production. Seed samples of SC-22 parental lines collected from company two and company one showed standard germination of 30.25 and 76.5%, respectively. The laboratory test indicated that majority of seed samples from different seed sources met the minimum requirements for hybrid maize seed standards.